2020
DOI: 10.3390/polym12010068
|View full text |Cite
|
Sign up to set email alerts
|

Fast Production of Cellulose Nanocrystals by Hydrolytic-Oxidative Microwave-Assisted Treatment

Abstract: In contrast to conventional approaches, which are considered to be energy- and time-intensive, expensive, and not green, herein, we report an alternative microwave-assisted ammonium persulfate (APS) method for cellulose nanocrystals (CNCs) production, under pressurized conditions in a closed reaction system. The aim was to optimize the hydrolytic-oxidative patented procedure (US 8,900,706), replacing the conventional heating with a faster process that would allow the industrial scale production of the nanomate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 70 publications
(84 reference statements)
1
10
0
Order By: Relevance
“…The XRD pattern of CNC powder revealed the characteristic peaks of crystalline cellulose I at 2θ = 15.1°, 16.5°, 22.5°and a weak peak at 34.4°. These peaks correspond to the (1 1 0), ( 110), ( 200) and (0 0 4) crystallographic planes, respectively, which are in agreement with different studies [19,34,35,40,42]. Chitosan films exhibited four diffraction peaks at 2θ = 8.12°, 11.4°, 18.0°, and a broad peak around 22.5°due to its semi-crystalline nature [9,19].…”
Section: Crystalline Structuresupporting
confidence: 89%
See 2 more Smart Citations
“…The XRD pattern of CNC powder revealed the characteristic peaks of crystalline cellulose I at 2θ = 15.1°, 16.5°, 22.5°and a weak peak at 34.4°. These peaks correspond to the (1 1 0), ( 110), ( 200) and (0 0 4) crystallographic planes, respectively, which are in agreement with different studies [19,34,35,40,42]. Chitosan films exhibited four diffraction peaks at 2θ = 8.12°, 11.4°, 18.0°, and a broad peak around 22.5°due to its semi-crystalline nature [9,19].…”
Section: Crystalline Structuresupporting
confidence: 89%
“…The bands observed in the range 1030-1161 cm −1 correspond to C\ \O stretching and C\ \H rocking vibrations of the pyranose ring [31]. Finally, the bands at 897 and 557 cm −1 are from β-glycosidic linkages in cellulose structure and O\ \H out of plane bending vibrations, respectively [18,23,35].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This observation can be verified in Figure 6 b, where crystallites size versus fractional variation in their interplanar distance (Δ d / d ) showed a significant but negative Pearson correlation of r = −0.99; p < 0.01. In literature, the importance of the potential variation between the distances of the crystalline planes in CNCs has been discussed, which affect properties in materials developed using these CNCs [ 52 ]. On the other hand, in the case of our data, the CNC yield may be related to the mechanical compression on the microfibrils during hydrolysis, and for this reason, the crystallite size decreases with increasing CNC yield ( Figure 6 c).…”
Section: Resultsmentioning
confidence: 99%
“…Amoroso et al examined the use of a microwave-assisted process to overcome the inefficiencies of heating currently used in the conventional APS process [ 39 ]. They found that controlling the heating ramp time and holding the heating time were important parameters to allow for sufficient time for the APS to convert to the active radical oxidant reacting with the biomass.…”
Section: Production Of Ccncsmentioning
confidence: 99%